After shock [videorecording]. (Pasig City : Viva Video Inc, 2003)
The earth shakes. Everything falls. Dreams are shattered. Lives are changed. From director Nikael Salomon comes a story of courage in the face of horror and human tragedy as New York City inhabitants are trapped in the crest of an unsuspected massive earthquake that destroys museums, skyscrapers, streets, subways, and brutally disassembles the Lady Liberty. As everyone searches in the ruins for their loved ones and hopes that they are safe, the Mayor is burdened not only with the thought of his family's safety but also with the destruction the earthquake has done in the city.